Silence Is Golden - Blythe, Paul W. (Canadian Journal of Counselling and Psychotherapy, 2012)
Many of us find ourselves in a leadership role with discussiongroups and other loosely defined teaching functions. We have all,at one time or another, experienced "that uncomfortable silence," and italways seems to be the responsibility of the leader to "jump in" and getthe thing going again. A leader who fails to come to the aid of a falteringgroup in this instance can engender a good deal of ire, indignation, anddisappointment on the part of the group members. Yet, an interjection bya leader at this point is usually unsatisfying to the leader as it is tantamountto a summation of the proceedings in a closing action on the issuesat hand. Groups tend not to start up easily after this point and leadershave to spend considerable time and effort to regenerate a productive levelof discussion. There is a third approach to the dilemma which I have tried,namely the legitimization of silence.